ANALYZE THE FACTORS IN IMPROVING EMPLOYEE PERFORMANCE - Sumarsid Sumarsid; Sri Mulyono; Azizah Azizah; Syech Idrus (International Journal of Economy, Education and Entrepreneurship, 2022)
The performance of employees is one of the most important factors in the company's progression. The enhancement of an employee's performance may receive support from either human resources or employee development. This new development in human resources will almost certainly affect employee performance. The goal of this study was to investigate the factors that play a role in enhancing the performance of employees. This qualitative research uses a case study approach based on phenomena, symptoms, facts, or social information. According to Sugiyono (2019), qualitative research methods are based on philosophy after positivism, which is used to examine the natural conditions of objects, where researchers are the main instrument, sampling sources from data sources, and data analysis is inductive or qualitative. In addition, the findings of qualitative research emphasize the concept of generalization. The findings indicate that the elements that impact employee performance are work pressure, communication, workload, and attitudes that contribute to work pressure, followed by the provision of Compensation that is not as expected by employees following working hours and employee guarantees. At the same time, efforts must make to improve performance, specific guidance and direction, training and development, and a discipline against company rules that are expected to improve employee performance